Political Journalism in the Conditions of Social System Change in Turkestan (Uzbekistan) - Namazova Nilufar Kambarkulovna (Periodica Journal, 2023)
The article deals with the newspapers published in Turkestan after the February Revolution, their attitude towards the Bolsheviks, the processes of organizing the press of the Soviets. In these processes, the political views of the contemporary enlightener Hadji Muin were studied on the basis of his articles published in the press.
Keywords: jadidism; enlightenment; press